2019
DOI: 10.3390/ijms20102539
|View full text |Cite
|
Sign up to set email alerts
|

The Dipeptidyl Peptidase-4 Inhibitor Linagliptin Ameliorates High-fat Induced Cognitive Decline in Tauopathy Model Mice

Abstract: Vascular risk factors, such as type 2 diabetes mellitus (T2DM), are associated with the increased risk of Alzheimer’s disease. One of the common T2DM medications, dipeptidyl peptidase (DPP)-4 inhibitors, have a minimum risk for hypoglycemia and have recently been suggested to ameliorate β-amyloid pathology. However, conflicting results have been reported regarding the effects of DPP-4 inhibition on cognitive function and tau pathology. Thus, we investigated whether inhibiting DPP-4 affects tau pathology and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…GLP-1RA showed obvious neuroprotective effect in neuronal cell lines [ 39 , 40 ], animal models [ 31 , 41 ] with or without diabetes mellitus and diabetic patients [ 42 ]. In this recent study, improved viability of PC12 cells with by AGEs (600μg/ml) at 48h and HT22 cells with by AGEs (400μg/ml) at 72h by liraglutide at a concentration of 200nM or 500nM were measured ( Figures 3F , 4F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1RA showed obvious neuroprotective effect in neuronal cell lines [ 39 , 40 ], animal models [ 31 , 41 ] with or without diabetes mellitus and diabetic patients [ 42 ]. In this recent study, improved viability of PC12 cells with by AGEs (600μg/ml) at 48h and HT22 cells with by AGEs (400μg/ml) at 72h by liraglutide at a concentration of 200nM or 500nM were measured ( Figures 3F , 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can reverse neuronal loss [ 30 ]. Additionally, it was showed that liraglutide improved cognition in non-diabetic individuals [ 31 ]. Owning to blood-brain barrier, large molecules, like semaglutide cannot reach the CNS, but liraglutide as a small molecule, can directly affect neurons in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…10,[27][28][29][30] The DDP4 inhibitor linagliptin also increased cerebral blood flow in AD mouse models. 31 Generally, the DPP4 inhibitors have been hypothesized to exert beneficial effects on cognition that are related to AD pathological mechanisms. This is consistent with the observed relationship with slower memory decline in patients with AD, and with their significantly larger associations with memory in cognitively normal APOE ε4 carriers, who may have accelerated early AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In animal and cell models, DPP4 inhibitors have been shown to increase hippocampal GLP1 levels, reduce hippocampal Aβ and p‐tau levels, alleviate Aβ plaque formation, and suppress neuroinflammation 10,27–30 . The DDP4 inhibitor linagliptin also increased cerebral blood flow in AD mouse models 31 . Generally, the DPP4 inhibitors have been hypothesized to exert beneficial effects on cognition that are related to AD pathological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that a DPP-4 inhibitor improved cognitive dysfunction by increasing the GLP-1 concentration in the brain [10,11]. Recently, Nakaoku et al also reported that linagliptin ameliorates high-fat induced cognitive decline in tauopathy model mice [29]. Several studies have demonstrated that GLP-1 alleviated learning and memory dysfunction [30] and that a GLP-1 analogue and GIP analogue prevented memory impairments [31,32].…”
Section: Effect Of Linagliptin On Microglial Activity and Mrna Expresmentioning
confidence: 99%